SOLUTIONS AND MEANS OF ALTERNATIVE TRANSPORT IN THE CONCEPT OF SUSTAINABLE DEVELOPMENT - CATALIN POPESCU; MARIUS BULEARCA (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2017)
The paper aims to achieve an overview of innovative initiatives on alternative transport in recent years in the context of increasing emissions of greenhouse gases. In this context are presented the main problems caused by motorized traffic in the urban agglomerations. Also, there are mentioned measures that could be implemented in busy urban areas. On this occasion are mentioned both new technical solutions and new means of alternative transport type. Additional, specific projects and programs are highlighted using bicycle transportation. There are mentioned initiatives regarding urban transportation completed in European projects such as: CIVITAS, EFFECTS etc. The examples and figures are mainly focused on Romania.